2020
DOI: 10.7202/1071516ar
|View full text |Cite
|
Sign up to set email alerts
|

Effet des classes et des écoles sur les performances en mathématiques des élèves de 4e année du primaire de la Province orientale en République démocratique du Congo

Abstract: Mesure et évaluation en éducation Effet des classes et des écoles sur les performances en mathématiques des élèves de 4e année du primaire de la

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
3
2
Order By: Relevance
“…They found out that the school explains 52% of the variance and the pupil 48% in 5 Francophone African countries. On the other hand, our results are far from those of Mokonzi et al, (2019) who found out that 71%, 16% and 13% of the total variance are located at the stude nt, class and school levels respectively. Also, the work of Thuku and Hungi (2013) who found out that 61.1%, 5.1% and 33.8% of the variance in mathematics achievement of Kenyan primary 6 students is at the pupil, class and school levels respectively.…”
Section: The Variability Of Scores At the Global Level: The Empty Modelcontrasting
confidence: 99%
See 4 more Smart Citations
“…They found out that the school explains 52% of the variance and the pupil 48% in 5 Francophone African countries. On the other hand, our results are far from those of Mokonzi et al, (2019) who found out that 71%, 16% and 13% of the total variance are located at the stude nt, class and school levels respectively. Also, the work of Thuku and Hungi (2013) who found out that 61.1%, 5.1% and 33.8% of the variance in mathematics achievement of Kenyan primary 6 students is at the pupil, class and school levels respectively.…”
Section: The Variability Of Scores At the Global Level: The Empty Modelcontrasting
confidence: 99%
“…The schools with the highest enrolment are those located in urban areas. This result is contrary to those of (Gershenson and Langbein, 2015;Jones et al, 2011) who found out that it does not have a significant effect on performance and those of (Mokonzi, 2019), who found a negative influence of class size on student performance in the Democratic Republic of Congo.…”
Section: • At the Classroom And School Levelcontrasting
confidence: 99%
See 3 more Smart Citations